Does TMS Disruption of the Left Primary Motor Cortex Affect Verb Retrieval Following Exposure to Pantomimed Gestures? - Murteira, Ana; Sowman, Paul F.; Nickels, Lyndsey (Frontiers in Neuroscience, 2018)
Previous research suggests that meaning-laden gestures, even when produced in the absence of language (i.e., pantomimed gestures), influence lexical retrieval. Yet, little is known about the neural mechanisms that underlie this process. Based on embodied cognition theories, many studies have demonstrated motor cortex involvement in the representation of action verbs and in the understanding of actions. The present study aimed to investigate whether the motor system plays a critical role in the behavioral influence of pantomimed gestures on action naming. Continuous theta burst stimulation (cTBS) was applied over the hand area of the left primary motor cortex and to a control site (occipital cortex). An action-picture naming task followed cTBS. In the naming task, participants named action pictures that were preceded by videos of congruent pantomimed gestures, unrelated pantomimed gestures or a control video with no movement (as a neutral, non-gestural condition). In addition to behavioral measures of performance, cTBS-induced changes in corticospinal activity were assessed. We replicated previous finding that exposure to congruent pantomimed gestures facilitates word production, compared to unrelated or neutral primes. However, we found no evidence that the left primary motor area is crucially involved in the mechanism underlying behavioral facilitation effects of gesture on verb production. Although, at the group level, cTBS induced motor cortex suppression, at the individual level we found remarkable variability of cTBS effects on the motor cortex. We found cTBS induction of both inhibition of corticospinal activity (with slower behavioral of responses) and enhancement (with faster behavioral responses). Our findings cast doubt on assumptions that the motor cortex is causally involved in the impact of gestures on action-word processing. Our results also highlight the importance of careful consideration of interindividual variability for the interpretation of cTBS effects.